PENERAPAN METODE HANIFIDA UNTUK MENINGKATKAN PEMAHAMAN SANTRI DALAM PEMBELAJARAN FURUDUL' AINIYAH DI WILAYAH AL MAWADDAH PONDOK PESANTREN NURUL JADID PAITON PROBOLINGGO - Faizatul Widat; Nur Aisyah; Indah Rohimah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to evaluate the application of the Hanifida Method in the learning of Furudul 'Ainiyah at the Nurul Jadid Islamic Boarding School, especially in the Al Mawaddah, Paiton, Probolinggo area, and to analyze its impact on students' understanding of Islamic inheritance law material. The research method used is qualitative with a descriptive approach, which involves interviews, observations, and document analysis as data collection techniques. The results of the study show that the application of the Hanifida Method can increase the involvement and understanding of students in the Furudul 'Ainiyah material. The use of methods that integrate theory with practice, as well as the use of auxiliary media such as diagrams and inheritance charts, makes it easier for students to understand concepts that were previously difficult to understand. However, this study also identified several challenges, such as time limitations in the learning schedule and differences in students' educational backgrounds that affect the speed of comprehension. Therefore, it is recommended that teachers continue to develop learning methods that are more applicable and practice-based, as well as manage learning time more efficiently in order to provide equal opportunities for all students to understand the material well. This research is expected to contribute to the development of more effective learning methods in Islamic boarding schools, especially in teaching the science of Furudul 'Ainiyah